QATTIQ JISMLARNING AYLANMA HARAKATINI O‘RGANISh - Turekeev, X.S. (SCIENCE and SOCIETY, 2025)
The article presents a method for determining the moment of inertia of solids using Maxwell's pendulum, using the law of conservation of energy. The transformation of energy from one type to another can be demonstrated practically. The results obtained can be compared with theoretically calculated values.
Keywords: time; height; speed; translational motion; rotational motion; moment of force; moment of inertia; energy